Analisis Usahatani Dan Pemasaran Bawang Prei Di Desa Torongrejo Kecamatan Junrejo Kota Batu - Robi, Mohammad Wildanir; Widodo, Wahyu; Sutawi, Sutawi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Leek is a type of vegetable that is widely grown in Indonesia. But there are still many problems faced by farmers, especially from income and marketing. Based on these problems, this study aims to analyze average revenue, average r/c and marketing efficiency. Methods: This research was conducted in Torongrejo Village, Junrejo District, Batu City. The samples used were 30 leek farmers, 3 collectors and 3 retailers. The data analysis used was quantitative descriptive analysis and r/c ratio analysis. The data used were primary data collected from respondents with questionnaires and interviews, while secondary data was used by taking data from the BPS Kota Batu. Results and discussion: The average income value received by leek farmers is IDR 41,529,701/period/ha, the average value of r/c ratio is 1.57, the marketing margin value at the wholesaler and retailer level is 25% and 12.50 % and the farmer share value received by farmers is 62.50%. Conclusion: The income value of leek farmers in Torongrejo Village is IDR 41,529,701, leek farming is feasible to continue with an r/c value of 1.57 and marketing efficiency in Torongrejo Village is efficient.